Antihypertensive Drugs: Are they Cost-Effective? - Chandra, Dr. Amrish (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Hypertension, also termed as high blood pressure, is long-term medical condition which is major cause of morbidity, mortality and needs lifelong treatment, also leads to complications such as stroke, myocardial infarction, and chronic kidney disease. A significant difference in cost of antihypertensive drugs is available in regulated (India) and less regulated market (United States). Objective: The objective of the study was to analyze price variation of unit dosage form manufactured by different companies for the same formulation with the same strength in both markets by calculation percentage price variation among the market. Materials and Methods: Cost of particular unit drug manufactured by different companies, in same strength was obtained from â€œCurrent Index of Medical Specialtiesâ€ and â€œIndian Drug Reviewâ€ for regulated market and from â€œGoodRXâ€ and â€œOnline Pharmaciesâ€ for less regulated market in both INR and USD. Results: Percentage price variation is less in the US than in India, but prices are extremely high. In India, the price of ACE inhibitor (Enalapril 2.5 mg) was found to be INR 0.60 (USD 0.009) whereas in the US market it was INR 178.81 (USD 2.7501). Conclusions: This wide price variation is due to payers, more labor cost, and less regulation schemes in less regulated market. Revision in price regulation is required to equalize prices in both markets.